Sistem Pendukung Keputusan Pemilihan Siswa Terbaik Pada Sekolah Menengah Atas Life Skill Teknologi Informatika Indo Global Mandiri dengan Metode Analitical Hierarchy Process - Sumarni Sumarni; Dhamayanti Dhamayanti (Jurnal Informatika Global)
ABSTRACTIGM LTI High School as an institution which is engaged in education every year holds an academic selection of the best students for class XII students. The selection of the best students at IGM LTI High School is still done conventionally. The Principal will hold a selection meeting of the best students with the teacher team every year. Assessment criteria for the best prospective students viewed from 1) academic values, namely : a). national test scores, b). end of semester tests, and c). report card grades; 2) non-academic grades; 3) moral values. This method requires need a long time, so that the best student selection decisions are less fast, effective, and efficient. Because of that, IGM LTI High School requires a desktop-based decision making system that supports the best student selection process. The best student selection decision making system is needed as an effort to improve the performance of the team of teachers and principals in the process of selecting the best students. Decision support system for selecting the best students in IGM LTI High School uses the Waterfall methodology with research tools consisting of: Data Flow Diagrams, Entity Relationship Diagrams and AHP (Analitycal Hierarchy Process) Methods. The testing method uses the Black Box method. This system was built using several lunk devices such as Visual Basic 6.0 and the Microsoft Access 2007 database. The results of this system will process the value of data and report the best students of class XII in IGM LTI High School.Keywords : Decision Support System, AHP,  Best StudentsABSTRAKSMA LTI IGM sebagai lembaga yang bergerak di bidang pendidikan setiap tahunn akademik mengadakan pemilihan siswa terbaik bagi siswa kelas XII.  Pemilihan siswa terbaik di SMA LTI IGM masih dilakukan secara konvensional. Kepala Sekolah akan mengadakan rapat pemilihan siswa terbaik degan tim guru setiap tahun. Kriteria penilaian calon siswa terbaik dilihat dari 1)  nilai akademik yaitu: a). nilai ulangan nasional, b). ulangan akhir semester, dan c). nilai rapor; 2) nilai non akademik; 3) nilai akhlak. Cara ini membutuhkan waktu yang lama, sehingga hasil keputusan pemilihan siswa terbaik kurang  cepat, efektif, dan efisien. Karena hal tersebut, SMA LTI IGM membutuhkan suatu sistem pengambilan keputusan berbasis desktop yang mendukung proses pemilihan siswa terbaik. Sistem pengambilan keputusan pemilihan siswa terbaik diperlukan sebagai upaya untuk peningkatan kinerja tim guru dan kepala sekolah dalam proses pemilihan siswa terbaik. Sistem pendukung keputusan pemilihan siswa terbaik di SMA LTI IGM menggunakan menggunakan metodologi Waterfall dengan alat-alat penelitian yang terdiri dari: Data Flow Diagram, Entity Relationship Diagram dan Metode AHP (Analitycal Hierarchy Process). Metode pengujian menggunakan metode Black Box. Sistem ini dibangun menggunakan beberapa perangkat lunk seperti Visual Basic 6.0 dan database Microsoft Access 2007. Hasil dari sistem ini akan memproses nilai data dan melaporkan siswa terbaik kelas XII di SMA LTI IGM.Kata kunci : Sistem Pendukung Keputusan, AHP,  Siswa Terbaik